Antitumor efficacy of silver nanoparticles reduced with β-D-glucose as neoadjuvant therapy to prevent tumor relapse in a mouse model of breast cancer - Moisés Armides Franco Molina; David Reding Hernández; Paola Leonor García Coronado; Jorge R. Kawas; Diana G. Zárate Triviño; Sara Paola Hernández Martínez; Beatriz Elena Castro Valenzuela; Cristina Rodríguez Padilla (Frontiers Media S.A., 2024)
Introduction: Neoadjuvant therapy constitutes a valuable modality for diminishing tumor volume prior to surgical resection. Nonetheless, its application encounters limitations in the context of recurrent tumors, which manifest resistance to conventional treatments. Silver nanoparticles (AgNPs) have emerged as a promising alternative for cancer treatment owing to their cytotoxic effects.Methods: Cellular viability was assessed by Alamar blue assay in 4T1 breast cancer cell line. Silver biodistribution was detected by an inductively coupled plasma optical emission spectrometer in an in vivo mice model. For neoadjuvant evaluation, mice were randomized and treated intratumoral with AgNPs-G or intraperitoneally with doxorubicin (DOX) as a control. Recurrence was determined after 170 days by counting lung metastatic nodules (dyed with Bouin solution) with histological confirmation by H&E. Masson's stain, Ki67 immunohistochemistry, and a TUNEL assay were performed in lungs from treated mice.Results: AgNPs-G reduced 4T1 cell viability and in an ex vivo assay the AgNPs-G decreased the tumor cell viability. After intravenous administration of AgNPs-G were detected in different organs. After intratumor administration, AgNPs-G are retained. The AgNPs-G treatment significantly reduced tumor volume before its surgical resection. AgNPs-G reduced the development of lung metastatic nodules and the expression of Ki67. TUNEL assay indicated that AgNPs-G didn't induce apoptosis.Conclusions: We concluded that intratumor administration of AgNPs-G reduced tumor volume before surgical resection, alongside a reduction in lung metastatic nodules, and Ki67 expression. These findings provide valuable insights into the AgNPs-G potential for intratumor and neoadjuvant cancer therapies. However, further research is needed to explore their full potential and optimize their use in clinical settings.